Bioequivalence and the food effect of macitentan/tadalafil 10/20 fixed‐dose combination tablets versus the use of single‐component tablets in healthy subjects - Jennifer Lynn Ford; Ahad Sabet; Jaya Natarajan; Hans Stieltjes; Daniel L. Chao; Navin Goyal; Denes Csonka (Wiley, 2024)
Abstract The primary aim was to demonstrate bioequivalence between the 10/20 mg fixed‐dose combination (FDC) of macitentan/tadalafil in a single tablet and the free combination of both drugs, and to evaluate the food effect on the 10/20 mg FDC in healthy participants. In this single‐center, randomized, open‐label, 3‐way crossover, single‐dose Phase 1 study in healthy adult participants, macitentan/tadalafil was administered as a 10/20 mg FDC formulation and compared with the free combination of macitentan and tadalafil. The food effect on the FDC was also evaluated. Pharmacokinetic sampling (216 h) was conducted. The 90% confidence intervals (CIs) for the geometric mean ratios of maximum observed plasma analyte concentration (Cmax) and area under the plasma analyte concentration-time curves (AUCs) for Treatment A (FDC, fasted) versus C (free combination, fasted) were within bioequivalence limits demonstrating that the FDC formulation can be considered bioequivalent to the free combination. The 90% CIs for the geometric mean ratios of Cmax and AUC for Treatment B (FDC, fed) versus A (FDC, fasted) were contained within bioequivalence limits demonstrating that there was no food effect. The administration of the 10/20 mg FDC was generally safe and well tolerated in healthy participants. This study demonstrated bioequivalence between the FDC of macitentan/tadalafil (10/20 mg) in a single tablet and the free combination of both drugs in healthy participants, and that the FDC can be taken without regard to food, similarly to the individual components. The FDC was generally safe and well tolerated.